The Role of Digitalization in Tourism Destination Marketing: A Literature Review - Marbun, April; Siringoringo, Benny; Simatupang, Jeslin; Simorangkir, Anita Lasria (CV. Kurnia Grup, 2024)
Digitalization has become a key driver in the transformation of the tourism industry, particularly in tourism destination marketing strategies. The development of digital technologies such as social media, online platforms, mobile applications, and smart tourism technologies has changed the way tourism destinations are promoted and managed. This study aims to examine the role of digitalization in tourism destination marketing through a literature review approach. The research method used in this study is a literature review, analyzing various scientific articles, research reports, and academic publications published between 2020 and 2024. The literature was collected through searches in academic databases using keywords related to digital tourism, destination marketing, and smart tourism. The collected data were analyzed using content analysis and thematic synthesis to identify trends, strategies, and challenges in the implementation of digitalization in tourism destination marketing. The results indicate that digitalization plays a significant role in enhancing the effectiveness of destination promotion, expanding tourism market reach, and strengthening destination image and competitiveness. Social media platforms, immersive technologies such as virtual reality and augmented reality, and big data utilization have become important components of digital tourism marketing strategies. However, the implementation of digitalization also faces several challenges, including limited digital literacy, technological infrastructure gaps, and data security concerns. Therefore, collaboration among governments, tourism industry stakeholders, local communities, and educational institutions is essential to support the development of a sustainable digital tourism ecosystem.